It's not supposed to be this way [compact disc, unabridged] : finding unexpected strength when disappointments leave you shattered - TerKeurst, Lysa (Thomas Nelson on BrillianceAudio., 2018)
New York Times best selling author Lysa TerKeurst unveils her heart amid shattering circumstances and tells listeners how to live assured when life doesn't turn out like they expected.